Socio-Economic Factors Affecting the Perception of Women Entrepreneurs towards Bank Loan: A Study on Rajshahi City - Karmakar, Anima; Habib, Sadia Nur; Ahmed, Atia (Asian Business Review, 2018)
This study conducted to focus the women entrepreneurs’ perception of how socio-economic factors influence at the time of taking a bank loan, whereas perception is the process by which an individual selects, organizes, and interprets stimuli into a meaningful and coherent picture of the world. The findings highlighted some socio-economic factors that influence women in taking a bank loan.  Data collected from women entrepreneurs’ residing in some major areas of the northern part of Bangladesh. A convenient sampling method was applied to collect response from 112 women entrepreneurs’ of which 105 found free from errors; those respondents used for the final study.Our study regarding the perception of the women reveals that religious view of our country, gender discrimination, and low educational qualification, lack of family support hinder their opportunity of taking a bank loan. Besides this research identify that advantageous living area & high social status help women at the time of taking a bank loan. Furthermore, the findings have established that financial solvency, bank’s rules & regulations, mortgage criteria and the nature of business carry significant influences on women entrepreneur in taking loan.The foremost contribution of the current study is that it focuses women’s observation and suggestion to break the barrier of getting the loan and find out a way to establish a positive attitude of the family as well as the society towards women entrepreneurs.
Keywords: Socio-Economic Factor; Women Entrepreneurs; Perception; Bank Loan